The Nature and Design of Post-Industrial Organizations - Huber, George P. (Management Science, 1984)
This paper describes the nature and design of post-industrial organizations. It begins with an assessment of the popular literature on post-industrial society, and finds that this literature is an inappropriate basis for inferring the nature of post-industrial organizations. Partly as a consequence of this finding, the paper turns to systems theory as a basis for determining both the nature of post-industrial society and the nature of the increased demands that this environment would impose on post-industrial organizations. The middle three sections of the paper describe design features that post-industrial organizations will employ to deal with these demands. In particular they examine designs for making more effective three processes that will exhibit increased importance in post-industrial organizations: (1) decision-making, (2) innovation, and (3) information acquisition and distribution. In addition to its conclusions concerning the design features that post-industrial organizations will possess, the paper sets forth three general conclusions. One of these is that, even though the aggregate of the demands on post-industrial organizations will be qualitatively greater than that experienced by previous organizations, there are design features that organizations can adopt that will enable them to cope with even worst-case loadings of these demands. A second conclusion is that the nature of the post-industrial environment will cause decision-making, innovation, and information acquisition and distribution to take on added importance in post-industrial organizations, and that one result of this will be that organizations will attempt to ensure routine effectiveness of these processes through increased formalization. In some cases this formalization will have as its purpose ensuring the existence of informal (or at least unstructured) activities, such as experimentation by “self-designing” organizations or acquisition of “soft” information by top managers. The third conclusion set forth is that during the current transition period between the industrial and post-industrial societies we can expect many organizations to fail, or to flee to less than wholly desirable niches, because they are ignorant of the post-industrial technologies, structures, and processes that would enable them to successfully engage the post-industrial environment and to become viable post-industrial organizations. It appears that an important task of organizational and management scientists during this period will be to aid in the development, transfer, and implementation of post-industrial design features and in this way help reduce the possibility of unnecessary failure or flight.